Managing Asian attractions, Generation Y and face. (September 2017) - Fyall, Alan; Leask, Anna; Barron, Paul; Ladkin, Adele
Abstract: In view of the growth, dynamism and increasing influence of the Asian tourism industry and the contribution to be played in the future by Gen Y visitors and workforce, this study compares and contrasts the views of professionals in the visitor attractions' sector in Asia. The research explores how they acknowledge Gen Y as a unique generational cohort worthy of attention and the strategies adopted by visitor attractions to meet this cohort's combination of needs, wants and expectations. The study provides a critical reflection on the usefulness of generational theory for studies of this nature and the contribution of "face" and "face consumption" as explanatory variables in the Asian context. The articles ends with a recommendation for a deeper, longitudinal approach to the further study of generational cohorts.